In the place of sanctity. Religious eminence in Jewish tradition - Ugo Volli (Ocula)
The concept of holiness is among the religious innovations brought by Christianity. In Hebrew there is a word (kadòsh) that normally translates as holy, but its usage is noticeably different, as it applies mostly to deities or entities such as the Land of Israel or the Jewish people and rarely to people. The paper aims to investigate whether some other categories of the Jewish tradition, such as the prophet, the sage (khakhàm), the pious (Hassìd), the righteous (tzaddìk) can be considered in some ways similar to the Christian definition of holiness. But differences are greater than similarities.